2001
DOI: 10.1046/j.1523-1755.2001.060002767.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluid and sodium removal on mortality in peritoneal dialysis patients

Abstract: Together, these findings suggest that removal of sodium and fluid is a predictor of mortality in PD patients, whereas Kt/V(urea) and TCC are not factors. Adequate fluid and sodium balance is crucial for the management of patients on PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
263
4
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(285 citation statements)
references
References 26 publications
12
263
4
5
Order By: Relevance
“…Whatever the explanation, this study suggests that clinicians need to pay close attention to APD patients who consistently achieve low UF volumes. This observation is in keeping with those from other recent studies, such as Ates et al (39), which suggested that the impact of loss of residual renal function on survival was due to its effect on salt and water removal and not the loss of small solute clearance.…”
Section: Discussionsupporting
confidence: 92%
“…Whatever the explanation, this study suggests that clinicians need to pay close attention to APD patients who consistently achieve low UF volumes. This observation is in keeping with those from other recent studies, such as Ates et al (39), which suggested that the impact of loss of residual renal function on survival was due to its effect on salt and water removal and not the loss of small solute clearance.…”
Section: Discussionsupporting
confidence: 92%
“…These peritoneal changes, coupled with loss of residual renal function, probably underlie the high prevalence of volume overload seen in many PD patients. Several studies (63)(64)(65) have shown an inverse relationship between daily peritoneal ultrafiltration volume and mortality, data that are consistent with the notion that reduced ultrafiltration capacity and consequent hypervolemia with increasing dialysis vintage may reverse the early survival advantage with PD.…”
Section: Possible Biologic Explanations For Differences In Outcomes Bsupporting
confidence: 60%
“…Hypervolemia is an important predictor of morbidity and mortality in PD patients (34). On the other hand, we did not find a correlation of endothelial dysfunction with residual renal functions, total fluid removal, and dialysis adequacy parameters.…”
Section: Discussioncontrasting
confidence: 86%